Evaluation of some rice genotypes for incidence of African rice gall midge and its parasitoid (P. Diplosisae) - Ogah, E.O.; Odebiyi, J.A.; Omoloye, A.A.; Nwilene, F.E. (2012)
African rice gall midge (AfRGM), Orseolia oryzivora Harris and Gagne, is one of the major insect pests of lowland/irrigated rice and could result in considerable economic damage. Host plant resistance and biological control appear to be the most promising control measures adopted so far. Three major rice genotypes (Oryza sativa, Oryza glaberrima and interspecific rice, New Rice for Africa (NERICA)) are cultivated in Nigeria. In two consecutive years (2008/09), field experiments were conducted at two eco-sites, using the genotypes to determine their influence on the incidence of the gall midge and percentage parasitism by Platygaster diplosisae, Risbec (Diptera: Platygateridae), an endoparasitoid that has been identified as the most important natural enemy of AfRGM. The AfRGM tiller infestation and parasitism by the parasitoid were significantly influenced (P< 0.05) by the rice genotypes for the two locations and seasons. Tropical Oryza glaberrima (TOG) lines showed the highest level of resistance to AfRGM attacks. TOG 7106 gave the highest level of resistance among the TOG lines. The NERICA lines were moderately, resistant with WAS127-IDSA-2-WAS-1-1-1 showing the highest level of resistance across the sites; while the Sativa lines were virtually susceptible to the midge attack across locations and years. ITA 306 recorded the highest level of infestation by the gall midge. However, none of the varieties showed complete resistant to AfRGM attacks. The parasitism by the parasitoid took the same trends as recorded for the gall midge infestation. Thus, integration of midge tolerant varieties with natural enemy enhances AfRGM management.